A MARKET MODEL FOR WATERMELON WITH SUPPLY UNDER RATIONAL EXPECTATIONS: AN EMPIRICAL STUDY ON BANGLADESH - Hoque, Md. Shahidul; Uddin, Mohammed Farid; Islam, Muhammad Alamgir (European Scientific Journal, ESJ, 2015)
The aim of this paper is to know the cultural practices and market model of watermelon in Bangladesh. The paper also attempts to identify the best model that may be used for forecasting purpose. Three models namely Naive, Cobweb and Rational Expectations (RE) have been considered by using time series agricultural data for a period of 2001/02 to 2012/13. Ordinary Least Square (OLS) and Two Stage Least Square (2SLS) estimation procedures have been used for estimation purpose. Reliable parameter estimates of the Naive, Cobweb and RE model with minimum standard errors, high explanatory power have been obtained in this research. Comparing all the models the RE is the best model, because most of the signs are expected and the results are plausible.